Identification and Characterization of Genes Involved in Leishmania Pathogenesis: The Potential for Drug Target Selection. (2nd June 2011) - Duncan, Robert; Gannavaram, Sreenivas; Dey, Ranadhir; Debrabant, Alain; Lakhal-Naouar, Ines; Nakhasi, Hira L.
Abstract : Identifying and characterizing Leishmania donovani genes and the proteins they encode for their role in pathogenesis can reveal the value of this approach for finding new drug targets. Effective drug targets are likely to be proteins differentially expressed or required in the amastigote life cycle stage found in the patient. Several examples and their potential for chemotherapeutic disruption are presented. A pathway nearly ubiquitous in living cells targeted by anticancer drugs, the ubiquitin system, is examined. New findings in ubiquitin and ubiquitin-like modifiers in Leishmania show how disruption of those pathways could point to additional drug targets. The programmed cell death pathway, now recognized among protozoan parasites, is reviewed for some of its components and evidence that suggests they could be targeted for antiparasitic drug therapy. Finally, the endoplasmic reticulum quality control system is involved in secretion of many virulence factors. How disruptions in this pathway reduce virulence as evidence for potential drug targets is presented.